(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The norms of behaviour amongst individuals in the kingdom’s society were set well before the18th century. Contemporaries who witnessed the nine-day celebrations (called Mahanavami) attest to thewidespread application of the Hindu caste system and the performance of animal sacrifices. The conflictbetween indigenous and imperial forces ultimately led to profound shifts in society. Although fightingbetween Hindu kingdoms and Sultanates persisted, conflicts between indigenous rulers (includingMuslims) and the newly arrived British were the most prominent. The influence of the English language,the advent of the printing press, and the critique of the established social order by Christianmissionaries all contributed to a more tolerant and adaptable culture. Mysore was affected by the samemodernization and nationalism that swept the rest of India.476 When the British Empire expanded theimportance of learning English, in addition to the native languages, rose to the forefront. The governor ofthe Mumbai Presidency, Lord Elphinstone, was responsible for these alterations. In 1841, his blueprintformalised the University Board’s foundational principles. As a result, the institution set up a branchspecifically for high school students. Schools were established in major cities to provide education tooutlying areas these schools were later upgraded to college standing, with each college serving as ahub for several neighbourhood institutions of learning known as zilla schools. The first schools teachingin English debuted in the city of Mysore in 1833 and quickly spread throughout the surrounding area.There were around 2,087 English-medium schools in the state of Mysore by 1881, after the establishmentof the department of education in 1858. Bangalore Central College opened in 1870 the Maharaja’sCollege in 1879 the Maharani’s College in 1901 the Mysore University in 1916 and St. Agnes College inMangalore in 1921 all of these institutions provided access to higher education.